De ontwerpen van A.J. Kropholler voor het raadhuis in Wateringen (Bulletin KNOB, 2011)
Alexander Jacobus Kropholler played a remarkable role in a very eventful period in Dutch architectural history. During the first half of the twentieth century discussions started between traditionally oriented architects and modern architects. As a conservative traditionalist, Kropholler played a fanatic role in these discussions. In spite of the rise of various modern architectural movements, he remained loyal to the traditional views on Dutch architecture. His marked views on architecture are expressed in his built and written oeuvre. In the numerous articles and books written by him he managed to criticize architecture in an idiosyncratic way and to communicate his own theories on architecture. On the basis of simple drawings he conveyed what is 'good' and what is 'bad' architecture as if he was making propaganda. Kropholler's role and the way in which he used his publications in the discussions in the thirties is further examined on the basis of an example.In the thirties Kropholler made the design for the town hall of the municipality of Wateringen. In honour of the occupation of the town hall in 1938 the municipality published a booklet in which three of Kropholler's remarkable design sketches are shown. The first two design sketches have a modern appearance and show similarities with designs of Kropholler's contemporaries, in particular the architect and urban planner Jos Klijnen (with whom Kropholler competed in the design contest for the town hall in Waalwijk in 1930) and with the architect Willem Marinus Dudok (several times Kropholler's rival in a design commission, such as the design contest for the new town hall in The Hague in the thirties). The third design is the realized design for the town hall in Wateringen and unlike the first two it has a traditional appearance. Apart from the fact that there are differences in the architecture of the design sketches, there are also distinct differences in the sketching technique. The first two design sketches are almost caricatures, whereas the third, realized, sketch has been worked out in great detail.Initially, it seems unlikely that Kropholler had anything to do with the two modern designs. Consequently, the question why the design sketches were published remains hard to answer. Assuming that the designs are indeed Kropholler's, the reason may be found by comparing Kropholler's own publications with the publication by the municipality of Wateringen. The propagandist way in which Kropholler manages to convey his own views on 'good' and 'bad' architecture in his own publications is comparable to the way in which the three design sketches for the town hall in Wateringen were published. In that case the fact that the two modern designs show similarities with designs of the two 'great' builders of town halls with whom Kropholler competed in the same contests during the thirties does not appear to be a coincidence. The publication of the municipality of Wateringen can be regarded as a distinct example of the way in which Kropholler wanted to convey his own ideas on architecture and the way in which he used his publications for that purpose.